2020
DOI: 10.1186/s12889-020-08755-w
|View full text |Cite
|
Sign up to set email alerts
|

Soil-transmitted helminthiasis in four districts in Bangladesh: household cluster surveys of prevalence and intervention status

Abstract: Background: In 2016, after 8 years of twice-annual nationwide preventive chemotherapy (PC) administration to school-age children (SAC), the Bangladesh Ministry of Health & Family Welfare (MOHFW) sought improved impact and intervention monitoring data to assess progress toward the newly adopted goal of eliminating soil-transmitted helminthiasis (STH) as a public health problem. Methods: We surveyed four Bangladeshi districts between August and October 2017. We conducted a multi-stage, cluster-sample, household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Another study demonstrated 0.6% of Trichuris trichiura ova, but Ascaris lumbricoides was 9% [ 112 ]. Other studies reported the prevalence of Ascaris lumbricoides and Trichuris trichiura ova as 1.5-8.2% and 0.8-0.9%, respectively [ 38 , 113 ]. In our research, a relatively low number of helminths was detected probably because of the urban setting of the study population, which may have had better sanitation and hygiene practices.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated 0.6% of Trichuris trichiura ova, but Ascaris lumbricoides was 9% [ 112 ]. Other studies reported the prevalence of Ascaris lumbricoides and Trichuris trichiura ova as 1.5-8.2% and 0.8-0.9%, respectively [ 38 , 113 ]. In our research, a relatively low number of helminths was detected probably because of the urban setting of the study population, which may have had better sanitation and hygiene practices.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated 0.6% of Trichuris trichiura ova, but Ascaris lumbricoides was 9% [102]. Another study reported prevalence of Ascaris lumbricoides and Trichiuris trichura ova was 8.2% and 0.9%, respectively [103]. In our research, the relatively low number of helminths was detected because of the urban setting of the study population, who probably had better sanitation and hygiene practices.…”
Section: Discussionmentioning
confidence: 41%
“…In each selected cluster, one segment was then randomly selected. The full methodology has been previously described in detail [ 19 ], and is also available on the CWW website ( https://childrenwithoutworms.org/icspm-reference-manual/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Since ICSPM produces an equal-probability sample of risk-group members within strata, all clusters in each district were selected from the same sampling frame, and analyses were kept separate for each district, no weight variables were added. One-sided 95% upper confidence limits (UCLs) were reported for measures of prevalence, including prevalence of MHII and HII, as the survey is designed to determine the lowest threshold under which the true prevalence lies [ 19 ]. Two-sided 95% confidence intervals (CIs) were calculated for all other estimates.…”
Section: Methodsmentioning
confidence: 99%